PENYULUHAN PENTINGNYA PEMENUHAN KEBUTUHAN GIZI PADA ANAK UNTUK MENCEGAH STUNTING DI WILAYAH KERJA PUSKESMAS KAMPUNG JABI KOTA BATAM - Erika Fariningsih; Yulinda Laska; Risma Ikha Paramitha; Desi Ramadhaniati; Dermonika Purba (Bajang Institute, 2023)
The purpose of the implementation of this outreach activity is so that mothers of toddlers who take part in the activity can understand and understand the importance of fulfilling nutrition in children to prevent stunting. The method used in this community service is to provide socialization in the form of counseling about the importance of fulfilling nutrition in children as an effort to prevent stunting. Participants in this activity are all mothers who have toddlers as many as 15 people. The evaluation of this socialization activity was that participants could understand the material presented, as evidenced by the enthusiastic participants in asking questions related to nutritional fulfillment. The result of this socialization activity is an increase in the knowledge and enthusiasm of the participants by participating in outreach activities on the importance of fulfilling nutrition in children.